Insan-i kamil and the Sufi vision of human perfection - Tanabayeva, A.; Niyazgulova А.; Alikbayeva, M.; Abdykaimova, N. (Eurasian Journal of Religious Studies, 2025)
The concept of the “Perfect Man” (Insan-i Kamil) occupies a central place in the metaphysical and spiritual framework of Islamic mysticism, particularly within the Sufi tradition. Rooted in Qur’anic anthropology and developed through the writings of prominent Sufi thinkers such as Ibn Arabi, Gazali, al-Jili, and Rumi, Akhmed Yassawi Insan-i Kamil represents the fully realized human being-one who mirrors divine attributes and serves as the bridge between the Creator and creation. The perfect human being embodies perfect knowledge, uniting intellectual comprehension (ma’rifa) and experiential, heartfelt knowledge (ma’rifat al-qalb). Sufi epistemology, drawing on Insan-i-kamil, asserts that true knowledge arises not through rational reasoning, but through the ontological transformation of the subject, achieved through the practices of spiritual discipline. Achieving this state is only possible when a person reveals their potential, which is based on unity and love with the Creator. Relevance of the pattern of a perfect person is important personal growth and spiritual perfection. Keywords: Insan-i Kamil, Sufism, tawḥid, divine attributes, Islamic mysticism